2020
DOI: 10.3390/rs12040612
|View full text |Cite
|
Sign up to set email alerts
|

Time Series Remote Sensing Data-Based Identification of the Dominant Factor for Inland Lake Surface Area Change: Anthropogenic Activities or Natural Events?

Abstract: Inland lake variations are considered sensitive indicators of global climate change. However, human activity is playing as a more and more important role in inland lake area variations. Therefore, it is critical to identify whether anthropogenic activity or natural events is the dominant factor in inland lake surface area change. In this study, we proposed a method that combines the Douglas-Peucker simplification algorithm and the bend simplification algorithm to locate major lake surface area disturbances. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…We found that the length of water pipe was correlated with an increase in surface area of lakes and canals, and precipitation correlated with an increase in surface area of seasonal rivers and streams. Liu et al (2020) [94] also found that anthropogenic variables had a stronger effect on lakes than natural variables, but they mainly found a negative effect on lake area change. This disparity may be explained by the fact that Liu et al ( 2020) focused on natural lakes, whereas our "lake" category included constructed lakes as well.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the length of water pipe was correlated with an increase in surface area of lakes and canals, and precipitation correlated with an increase in surface area of seasonal rivers and streams. Liu et al (2020) [94] also found that anthropogenic variables had a stronger effect on lakes than natural variables, but they mainly found a negative effect on lake area change. This disparity may be explained by the fact that Liu et al ( 2020) focused on natural lakes, whereas our "lake" category included constructed lakes as well.…”
Section: Discussionmentioning
confidence: 99%
“…Characterizing how and where lakes are changing on broad scales is, therefore, critical to understanding the drivers of change. However, studies that have investigated patterns of waterbody surface area change, rather than quantifying variability or linear change, are typically performed on short-term time series (∼2 years), long-term but low-resolution time series (i.e., only five measurements in 22 years), or on few (<30) waterbodies. Recently, the Reservoir and Lake Surface Area Time series (ReaLSAT) data set, a long-term, spatially extensive water body data set, has become available which makes possible, using new analytic tools, a comprehensive analysis of long-term patterns of change across broad spatial scales.…”
Section: Introductionmentioning
confidence: 99%
“…The delineation of waterbodies provides an object-based analysis, which characterises the dynamics of the whole waterbody, not its individual pixels. This allows analysis of waterbody characteristics such as the change in surface area over time [24,33], facilitating study of the events observed to be impacting individual waterbodies [33]. This in turn allows environmental water managers to evaluate the efficacy of environmental flow events in providing aquatic ecosystem provision objectives [34].…”
Section: Introductionmentioning
confidence: 99%